RESILIENCE AS RESISTANCE: POLITICAL DISCOURSES OF CLIMATE ADAPTATION AMONG SMALLHOLDER COFFEE FARMERS IN FOREST CONFLICT ZONES OF CENTRAL ACEH INDONESIA - Hajad, Vellayati; Ikhsan, Ikhsan; Zafira, Nabila Hilmy; Dewi, Sarini Vita; Sari, Irma Permata (Universitas Padjadjaran, 2025)
Climate change has exerted significant social, economic, and environmental pressures on small-scale coffee farmers, particularly those living near protected forest areas. Declining yields, land limitations, and restrictive conservation policies have created complex tensions related to resource access and survival strategies. This study aims to analyze the political discourses embedded in the dynamics of land rights disputes and climate adaptation strategies of small-scale coffee farmers. Using a qualitative approach and Critical Discourse Analysis (CDA), the study explores how farmers negotiate, reject, and reinterpret state environmental regulations through everyday practices and narratives. This study’s findings reveal that coffee farmers’ adaptation strategies are not merely technical responses to climate change, but also reflect resistance to dominant power structures. This process includes contesting land authority, territorializing space within the conservation framework, and recognizing the often marginalized identities of farmers. The conclusion of this research shows that the resilience of coffee farmers can be understood as a form of resistance, reflecting negotiations and opposition to dominant discourses, as well as their efforts to reclaim their living spaces increasingly threatened by exclusive conservation policies.